2016
DOI: 10.1002/mrd.22673
|View full text |Cite
|
Sign up to set email alerts
|

Expression and regulation of the differentiation regulators ERBB Receptor Feedback Inhibitor 1 (ERRFI1) and Interferon‐related Developmental Regulator 1 (IFRD1) during the periovulatory period in the rat ovary

Abstract: The current study investigated the regulation and the spatiotemporal expression pattern of Errfi1 and Ifrd1, genex encoding factors that regulate differentiation and cessation of cell division, in the rat ovary during the periovulatory period. Immature female rats (22-23 days old) were injected with pregnant-mare serum gonadotropin to stimulate folliculogenesis, followed by human chorionic gonadotropin (hCG) to induce ovulation. Ovaries, granulosa cells, theca-interstitial cells, or cumulus oocyte complexes (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 52 publications
0
3
2
Order By: Relevance
“…3). This is in contrast to a study in female Sprague-Dawley rats, where increased expression of IFRD1 was found in granulosa cells and cumulus oocyte complexes after administration of human chorionic gonadotropin (to mimic the LH-surge and induce ovulation), indicating potential involvement of IFRD1 in oocyte maturation (Li et al, 2016). However, this study was performed in a different time frame (hours) and on single cells compared with weeks and ovary homogenates, respectively, in our study.…”
Section: Ovarycontrasting
confidence: 99%
“…3). This is in contrast to a study in female Sprague-Dawley rats, where increased expression of IFRD1 was found in granulosa cells and cumulus oocyte complexes after administration of human chorionic gonadotropin (to mimic the LH-surge and induce ovulation), indicating potential involvement of IFRD1 in oocyte maturation (Li et al, 2016). However, this study was performed in a different time frame (hours) and on single cells compared with weeks and ovary homogenates, respectively, in our study.…”
Section: Ovarycontrasting
confidence: 99%
“…However, studies in rats showed the link between obesity and the lack of a preovulatory surge of progesterone and LH which consequently causes a decrease in the expression of the Edn2 gene [ 36 ]. Errfi1 may be important for theca and granulosa cell differentiation and the cumulus–oophorus complex (COC) expansion [ 125 ]. Tnfaip6 is involved in forming the extracellular matrix (ECM) during cumulus mucification.…”
Section: High-fat Diet Affecting Ovarian Folliculogenesismentioning
confidence: 99%
“…The expression of IFRD1, a gene proposed to be involved in regulation of cell proliferation and differentiation (Vadivelu et al 2004;Vietor & Huber 2007), decreased in time point 3 compared to time point 1 for all females, as in Chapter 4, but significantly for the early egg-laying females ( Figure 5.3) . This is in contrast with a study in female Sprague-Dawley rats, where increased expression of IFRD1 was found in granulosa cells and cumulus oocyte complexes after administration of human chorionic gonadotropin (to mimic the LH-surge and induce ovulation), indicating potential involvement of IFRD1 in oocyte maturation (Li et al 2016). However, this study was performed in a different time frame (hours) and on single cells compared to weeks and ovary homogenates, respectively in our study.…”
Section: Ovarycontrasting
confidence: 93%